2010
DOI: 10.1177/1740774510374973
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of factors associated with premature trial closure and feasibility of accrual benchmarks in phase III oncology trials

Abstract: Background A major challenge for randomized phase III oncology trials is the frequent low rates of patient enrollment, resulting in high rates of premature closure due to insufficient accrual. Purpose We conducted a pilot study to determine the extent of trial closure due to poor accrual, feasibility of identifying trial factors associated with sufficient accrual, impact of redesign strategies on trial accrual, and accrual benchmarks designating high failure risk in the clinical trials cooperative group (CTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
84
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 21 publications
(33 reference statements)
2
84
0
Order By: Relevance
“…The 21% observed enrollment rate among both cases and controls was somewhat lower than the 27% historical enrollment reported by Schroen et al 10 for NCI-supported non-therapeutic trials performed by the Clinical Trials Cooperative Group. Based on the most frequently cited reasons offered by the subjects who declined enrollment, institutional access was cited most frequently by those declining participation.…”
Section: Rationale For Undertaking a Process Feasibility Studymentioning
confidence: 41%
See 3 more Smart Citations
“…The 21% observed enrollment rate among both cases and controls was somewhat lower than the 27% historical enrollment reported by Schroen et al 10 for NCI-supported non-therapeutic trials performed by the Clinical Trials Cooperative Group. Based on the most frequently cited reasons offered by the subjects who declined enrollment, institutional access was cited most frequently by those declining participation.…”
Section: Rationale For Undertaking a Process Feasibility Studymentioning
confidence: 41%
“…8 Several recent studies examining accrual to federally funded treatment trials reported that 50% to 80% of trials did not achieve the projected accrual goals within the proposed accrual timeframe, and over one-third failed to meet minimum accrual goals at the time of closure. 9,10 Notably, among 82 cancer trial cooperative group trials, therapeutic trials had superior accrual to non-therapeutic trials (59% vs. 27%, P=0.05). 10 Importantly, the group indicated that those studies that conducted pre-trial accrual assessment achieved higher rates of sufficient accrual compared to those studies that did not (67% vs 47%) and emphasized a need to identify approaches that more accurately identify accrual to clinical studies.…”
Section: Rationale For Undertaking a Process Feasibility Studymentioning
confidence: 99%
See 2 more Smart Citations
“…At a single institution, she observes that more than half of phase III trials closed to insufficient accrual (3). Similarly, Go and colleagues (4) reported that "over a quarter of the trials" of all Eastern Cooperative Oncology Group (ECOG) phase II and phase III trials from 1977 to 2006 failed to achieve accruals goals and complete.…”
mentioning
confidence: 99%